2007
DOI: 10.1080/07399330701465184
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Migration on HIV Prevention for Women: Constructing a Conceptual Framework

Abstract: There are an estimated 40.5 million people currently living with HIV globally, 17.5 million of whom are women, according to the AIDS Epidemic update: December 2005, conducted by UNAIDS and the World Health Organization (WHO) 2005. Women are vulnerable to HIV for biologic as well as social reasons. In the past, the HIV prevention theorists have not considered the context of women's lives: factors at the individual, relationship, and community levels, as well as structural factors (both policy and cultural) impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…The vulnerability can also be atributed to male partners' sexual inidelity having concurrent and multiple sexual partnerships and the lack of condom use which exemplify the link between internal migration and HIV vulnerability and not just international migration which has been the focus of many studies. Therefore, this chapter conirms Webber's [59] assertion that women's biological as well as their social vulnerabilities to the pandemic may be exacerbated within the context of international labour migration and rural-urban migration [4]. The scourge of HIV and AIDS is a complex, multifaceted issue that requires a collaborative efort and hence multidimensional strategies.…”
Section: Hiv/aids -Contemporary Challenges 154mentioning
confidence: 77%
“…The vulnerability can also be atributed to male partners' sexual inidelity having concurrent and multiple sexual partnerships and the lack of condom use which exemplify the link between internal migration and HIV vulnerability and not just international migration which has been the focus of many studies. Therefore, this chapter conirms Webber's [59] assertion that women's biological as well as their social vulnerabilities to the pandemic may be exacerbated within the context of international labour migration and rural-urban migration [4]. The scourge of HIV and AIDS is a complex, multifaceted issue that requires a collaborative efort and hence multidimensional strategies.…”
Section: Hiv/aids -Contemporary Challenges 154mentioning
confidence: 77%
“…The separate analyses were compared to determine strong emerging themes from the data, and these findings are documented here with illustrative quotations from the research participants. We have used a eco-social conceptual framework as our theoretical model [11,12].By this we mean that women are viewed as making choices within the environmental and social contexts in which they live their lives.…”
Section: Methodsmentioning
confidence: 99%
“…This phenomenon has been well described for populations of women migrants in a diversity of situations (Webber, 2007), and for rural-to-urban migrants of both genders in China (Hong et al, 2006;Hu, Liu, Li, Stanton, & Chen, 2006;Yang, Derlega, & Luo, 2007). Internal migration in Cambodia is a common phenomenon (Maltoni, 2006), and poverty is the main impetus for rural-to-urban migration in Cambodia (Nareoun, 2004).…”
Section: Context Of Migration and The Hiv Epidemic In Cambodiamentioning
confidence: 99%
“…A review of the international literature (Webber, 2007) has demonstrated that women who have migrated within their country or across international borders are particularly vulnerable to HIV as a result of limited access to health care, the change in norms and social supports in their new environments, and, as was found by Nishigaya (2002), lack of sufficient income that results in the economic need for generating income through sex work. Health care access provides opportunities for education about safer sexual relations, access to condoms, and early diagnosis and treatment of sexually transmitted infections that may contribute to HIV vulnerability.…”
Section: International Literature On Migrant Women and Hivmentioning
confidence: 99%
See 1 more Smart Citation